PENGARUH LATIHAN TENDANGAN LURUS MENGGUNAKAN BEBAN TERHADAP POWER OTOT TUNGKAI PADA PESILAT PUTRA PERGURUAN SATRIA MUDA INDONESIA KOTA PEKANBARU - Ismanto, Agus; Slamet, Slamet; Vai, Aref (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: Based on the results of observations at the pencak silat Satria Muda Indoesia putra pekanbaru school, it can be seen that athletes are still not maximal in straight kicks, this proves when they practice and compete with the lack of leg muscle strength of athletes so they are not maximal are for straight kicks, straight kicks can still be avoided and read by opponents, this is due to a lack of speed and power when performing a straight kick. The aim of this study was to determine the effect of straight-kick training with the help of the load effect on leg muscle in male university fighter Satria Muda Indonesia Kota Pekanbaru. the population is 12 people, so the author takes everything that should be used as a sample in this study, the determination of the sample using the total sampling method. The instruments used in this study were standing jump tests, data retrieval techniques were obtained from the pre-test and post-test. Before the analysis, the pre-test was performed with an average yield of 204.58. A straight stair exercise was then carried out with a load of 16 meetings about the male hunter of the Indonesian Juvenile Prison Group Pekanbaru, with a total of 12 people and the average after the test 208.25. Based on data analysis pre-test and post-test, there are differences in numbers that increase or increase by 3.67. And based on the t-test analysis, tcount produces 8.33 and t table 1.782. Does not mean> t table. Based on the results of the analysis, it can be concluded as follows: there is an influence between straight kick training using the load (X) on leg muscle strength (Y) on the male hunter of the Pekanbaru Indonesian young satria college.Key Words: Straight Kick, Load, Leg Muscle Power